(untitled) (Research, Society and Development, 2023)
Children and young people should have access to human rights education (HRE) and that schools are one of the main means by which HRE should be made available. However, there is currently limited knowledge about the presence and form of EDH in school contexts, and there are no means by which the provision of EDH in schools is to be evaluated. This article proposes a theoretical framework to support the classification of teaching responsibilities in relation to EDH and argues that a systemic change in education systems is needed so that the provision of EDH is carried out more widely and consistently. The viability of the developed framework was then tested by applying it to the results of these analyses. The theoretical contribution made by the document deepens knowledge and understanding about the nature of the responsibilities assigned to teachers to educate students about human rights and provides a basis for stimulating debate on what constitutes effective practices of school HRE.